Preparing for skill transfer: a decision tree tool for curriculum design and assessment of virtual offshore emergency egress training. (1st September 2020) - Smith, Jennifer; Musharraf, Mashrura; Blundon, Allison; Veitch, Brian
ABSTRACT: To prepare personnel for offshore emergencies, safety training should focus on transferability. Virtual environment (VE) training is designed to support the transfer of acquired egress skills to novel offshore emergencies. Decision trees (DT) are useful tools to evaluate training transfer. DTs use performance data collected during VE training to model participants' behavioural patterns. A DT that reflects ideal behaviour is used as a benchmark to compare the compliance of the participants' data-informed behavioural patterns. Employing the diagnostic and predictive capabilities of DTs can indicate whether a person is capable of responding to a wide variety of emergencies using inference. This paper demonstrates the use of DTs as a curriculum design and assessment tool to determine if the VE training adequately prepared participants to transfer their egress skills to new emergencies in the same virtual setting.